Study of Building Maintenance Against User Convenience of the Kandilo Plaza Shopping Center Building - Oryza Lhara Sari; B Basyaruddin; Rahmawati Aulia (Universitas Islam Sultan Agung, 2021)
The world of construction will definitely not be separated from the maintenance and maintenance of the building. As for what is meant by maintenance (maintenance) is a way to maintain the function of the building itself. Maintenance (maintenance) on the building is very influential when the building is completed or built and will be used for the activities of building users. The data obtained were analyzed using multiple linear regression analysis method, with the help of SPSS application. The results showed that the building maintenance carried out by the management of the Kandilo Plaza shopping center building was classified as good, although there were still a few that needed to be repaired. Based on the testing and data processing, the results obtained sig = 0.000 < = 0.05, which means that simultaneously the architectural, structural, mechanical and electrical component variables have a significant effect on the comfort of users and building visitors with an effect of 17.2%. In addition, for partial testing, the results of each building maintenance variable affect the comfort level of visitors.